Peningkatan Kompetensi Mahasiswa Calon Guru Matematika dalam Mengembangkan Media Pembelajaran Berbasis Mobile Learning - Dindin Sobiruddin; Dedek Kustiawati; Gelar Dwirahayu; Gusni Satriawati; Khamida Siti Nur Atiqoh (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2022)
The purpose of this study is to enhance of mathematics undergraduate students’ pedagogic competency by providing assistance in the development of learning media in mathematics. The research method is action research which includes four stages: pre-research analysis, reflection, preparation and implementation of actions, and evaluation. The instrument is questionnaire of validation by media experts (content / material) and practitioner in education. The research was conducted in 2019/2020 with 15 students of mathematics education study program who have computer skills. The results shows that an assistance for undergraduate students is effective to improving their competences specially in pedagogy integrated to technology mobile learning. Based on expert judgments the nine learning media based smartphone in mathematics was produced in this study showed the